Speaking without permission: metaphor, media, and the framing of Black women's vice-presidential leadership in Ghana and the United States - Donkor, Felicity, author; Anderson, Karrin, advisor; Gibson, Katie, committee member; Martey, Rosa, committee member (Colorado State University. Libraries, 2025)
In the course of four years, two Black women—one in the United States, the other in Ghana—accepted their nominations as vice-presidential candidates, rewriting expectations for leadership and representation. Through comparative rhetorical analysis, this thesis assesses how Kamala Harris and Jane Naana Opoku-Agyemang used metaphors in their vice presidential nomination speeches to shape their political identities and how media outlets with differing ideological leanings interpreted or challenged these identities. I carefully combine metaphorical analysis and media framing analysis to examine how mainstream media outlets in the US and Ghana echoed or resisted their political identities. I argue that these speeches, while grounded in distinct cultural and political traditions, form a transnational subgenre of rhetorical performance that simultaneously responds to and reshapes dominant ideas of leadership. This thesis reveals how metaphors, media, and gender intersect to constitute Black women's political speech as both contested and constitutive across borders.